Catalogue of aquatic Oligochaeta (Annelida: Clitellata) of Montenegro, exclusive of Naidinae and Pristininae - Šundić, Danijela; Radujković, Branko M.; Krpo–Ćetković, Jasmina (Zootaxa, 2011)
The aquatic oligochaete fauna of Montenegro was recently studied in order to improve the knowledge of this group in the Balkan region. This study was carried out on sediments collected from 70 sampling sites (the Black Sea and the Adriatic Sea drainage basins) during three years (2005–2008). Forty-one species were identified, from seven following families: Naididae, Enchytraeidae, Haplotaxidae, Lumbriculidae, Lumbricidae, Criodrilidae and Branchiobdellidae (exclusive of Naidinae and Pristininae). Sixteen of them represent first record for the Montenegrin oligochaete fauna: Embolocephalus velutinus, Ilyodrilus templetoni, Psammoryctides deserticola, Spirosperma ferox, Tubifex ignotus, Bathydrilus adriaticus, Bothrioneurum vejdovskyanum, Rhyacodrilus coccineus, Cernosvitoviella atrata, Enchytraeus buchholzi, Mesenchytraeus armatus, Haplotaxis gordioides, Rhynchelmis limosella, Stylodrilus heringianus, Tatriella slovenica and Trichodrilus strandi. The list of species from the subfamilies Naidinae and Pristininae was published previously (Šundić et al. 2011), and it comprises 36 species. Altogether, the present study and literature data show that Montenegrin aquatic oligochaete fauna consists of 77 species. Concerning similarity, values of Jaccard’s index are the highest between Montenegrin and Serbian oligochaete fauna (57 %), and the lowest between Montenegrin and Albanian oligochaete fauna (27.77 %). Species richness estimators (Mao Tau, Uniques Mean, Chao 1, Chao 2, Jack 1, Jack 2, Bootstrap, ACE and ICE) indicate that findings of new oligochaete species in Montenegro are expected.